Bioreducible Polymer Micelles Based on Acid-Degradable Poly(ethylene glycol)-poly(amino ketal) Enhance the Stromal Cell-Derived Factor-1α Gene Transfection Efficacy and Therapeutic Angiogenesis of Human Adipose-Derived Stem Cells - Lee, Tae-Jin (Int J Mol Sci, 2018)
Adipose-derived stem cells (ADSCs) have the potential to treat ischemic diseases. In general, ADSCs facilitate angiogenesis by secreting various pro-angiogenic growth factors. However, transplanted ADSCs have a low therapeutic efficacy in ischemic tissues due to their poor engraftment and low viability. Stromal cell-derived factor-1α (SDF-1α) improves the survival rate of stem cells transplanted into ischemic regions. In this study, we developed acid-degradable poly(ethylene glycol)-poly(amino ketal) (PEG-PAK)-based micelles for efficient intracellular delivery of SDF-1α plasmid DNA. The SDF-1α gene was successfully delivered into human ADSCs (hADSCs) using PEG-PAK micelles. Transfection of SDF-1α increased SDF-1α, vascular endothelial growth factor, and basic fibroblast growth factor gene expression and decreased apoptotic activity in hADSCs cultured under hypoxic conditions in comparison with conventional gene transfection using polyethylenimine. SDF-1α-transfected hADSCs also showed significantly increased SDF-1α and VEGF expression together with reduced apoptotic activity at 4 weeks after transplantation into mouse ischemic hindlimbs. Consequently, these cells improved angiogenesis in ischemic hindlimb regions. These PEG-PAK micelles may lead to the development of a novel therapeutic modality for ischemic diseases based on an acid-degradable polymer specialized for gene delivery.